The validity of self-reported vs. measured body weight and height and the effect of self-perception - Gokler, Mehmet Enes (Arch Med Sci, 2016)
INTRODUCTION: The objective was to assess the validity of self-reported body weight and height and the possible influence of self-perception of body mass index (BMI) status on the actual BMI during the adolescent period. MATERIAL AND METHODS: This cross sectional study was conducted on 3918 high school students. Accurate BMI perception occurred when the student’s self-perception of their BMI status did not differ from their actual BMI based on measured height and weight. Agreement between the measured and self-reported body height and weight and BMI values was determined using the Bland-Altman metod. To determine the effects of “a good level of agreement”, hierarchical logistic regression models were used. RESULTS: Among male students who reported their BMI in the normal region, 2.8% were measured as overweight while 0.6% of them were measured as obese. For females in the same group, these percentages were 1.3% and 0.4% respectively. Among male students who perceived their BMI in the normal region, 8.5% were measured as overweight while 0.4% of them were measured as obese. For females these percentages were 25.6% and 1.8% respectively. According to logistic regression analysis, residence and accurate BMI perception were significantly associated with “good agreement” (p ≤ 0.001). CONCLUSIONS: The results of this study demonstrated that in determining obesity and overweight statuses, non-accurate weight perception is a potential risk for students.